KEKERASAN SIMBOLIK DENGAN STRATEGI PENGONOTASIAN DAN PENGIASAN (SYMBOLIC VIOLENCE WITH CONNOTATIONS AND FIGURE OF SPEECH STRATEGIES) - Roekhan Roekhan (Universitas Lambung Mangkurat, 2013)
AbstractSymbolic Violence with Connotations and Figure of Speech Strategies. Symbolic violenceis the imposition of vague meaning, logic bias, and the bias that it was accepted by thereader as the meaning is clear, the logic is right, and positive values . Connotationstrategy in the form of symbolic violence packaging information with the word, phrase,or statement implies connotations, meaning evaluative or emotive meaning. Connotationstrategy used to (a) raise, (b) degrading, (c) strengthening, and (d) weaken information.The figure of speech strategy is to wrap the information with figurative language. Thefigure of speech strategies used are of two kinds, namely: (a) figure of speech direct(metaphor) and (b) figure of speech indirect.Keywords: symbolic violence,connotation strategy, figure of speech strategy,figuratively direct, indirect allusionAbstrakKekerasan Simbolik dengan Strategi Pengonotasian dan Pengiasan. Kekerasan simbolikadalah pemaksaan makna kabur, logika bias, dan nilai bias agar hal itu diterima olehpembaca sebagai makna yang jelas, logika yang benar, dan nilai yang positif. Strategipengonotasian dalam kekerasan simbolik berupa pengemasan informasi dengan kata,ungkapan, atau pernyataan yang mengandung makna konotasi, makna evaluatif, ataumakna emotif. Strategi pengonotasian digunakan untuk (a) meninggikan, (b)merendahkan, (c) menguatkan, dan (d) melemahkan informasi. Strategi pengiasanadalah membungkus informasi dengan bahasa kias. Strategi pengiasan yang digunakanada dua macam, yaitu (a) pengiasan langsung (pemetaforaan) dan (b) pengiasan tidaklangsung.Kata-kata kunci: kekerasan simbolik, strategi pengonotasian, strategi pengiasan, kiasanlangsung, kiasan tidak langsung